Distributed leadership in public service organizations - Jakobsen, Mads Leth Felsager; Kjeldsen, Anne Mette; Pallesen, Thomas (Politica, 2016)
During the past two decades there has been increased interest in collective or distributed forms of leadership within generic leadership theory and organizational psychology. “Distributed leadership” describes the sharing of leadership tasks between employees and managers with the aim to influence decision making, resource availability, and goal setting within an organization. This article introduces the concept of distributed leadership to the public administration literature and empirically examines the relevance of this leadership constellation for different public organization performance measures. Using survey and archival data collected at one of Denmark’s largest public hospitals, the analysis shows that hospital wards with high levels of distributed leadership also have employees who are more satisfied and innovative and who report higher levels of performance. Moreover, distributed leadership seems to be positively related with lower sickness absence among hospital employees. This indicates that distributed leadership is a relevant leadership constellation in public service producing organizations.